Implementing cbi lessons to develop 9 th grade students’ reading comprehension skills (2023)
Eng: This Action Case Study implemented a Content-Based Instruction (CBI) approach to enhance the reading comprehension skills of ninth-grade students in a Colombian public school. The focus was on health-themed lessons, assessing their impact on literal, inferential, and critical reading skills with lengthy informative texts. Qualitative methods, including a diagnostic test, researcher observations, and the researcher journal, were employed over few weeks. Results showed improved comprehension and expanded health vocabulary through discussions and posters. However, challenges persisted in fully summarizing main ideas, emphasizing the need for enhanced strategic processing. The study highlights the effectiveness of CBI in bolstering reading skills, shedding light on areas for further improvement in strategic processing to enhance working memory and information retention. Spa: Este estudio de caso de acción implementó un enfoque de instrucción basada en contenidos (CBI) para mejorar las habilidades de comprensión lectora de estudiantes de noveno grado en una escuela pública colombiana. La atención se centró en lecciones con temas de salud, evaluando su impacto en las habilidades de lectura literal, inferencial y crítica con textos informativos extensos. Durante algunas semanas se emplearon métodos cualitativos, incluida una prueba de diagnóstico, observaciones del investigador y el diario del investigador. Los resultados mostraron una mejor comprensión y un vocabulario de salud ampliado a través de debates y carteles. Sin embargo, persistieron los desafíos para resumir completamente las ideas principales, enfatizando la necesidad de un mejor procesamiento estratégico. El estudio destaca la eficacia de la CBI para reforzar las habilidades de lectura, arrojando luz sobre áreas que necesitan mejoras adicionales en el procesamiento estratégico para mejorar la memoria de trabajo y la retención de información.